THE CONSTRUCTION OF NETIZENS’ SOCIAL PRACTICES IN THE DIGITAL ARENA: A PIERRE BOURDIEU ANALYSIS OF VIRAL PUBLIC ISSUES - Lilis Sariyanti; Desti Ariani; Rahmat Agustina D (Jurnal Society : Pengamat Perubahan Sosial, 2026)
The rapid growth of social media has transformed netizens from passive consumers of information into active social actors who shape public opinion and exercise social control within the digital arena. This study aims to examine the social practices of netizens in responding to viral public issues in Indonesia through Pierre Bourdieu's theoretical framework, particularly the concepts of habitus, capital, and field. Employing a qualitative approach, the study applies content analysis to three prominent viral cases: the controversy surrounding the revision of the Indonesian National Armed Forces (TNI) Law (2024), the Ferdy Sambo case (2022), and the Mario Dandy case (2023). Data were collected from social media posts, netizens' comments, reposts, and relevant literature, and were analyzed interpretively within a critical constructivist paradigm. The findings reveal that netizens can mobilize social capital, including digital networks, collective solidarity, and interaction intensity, into symbolic capital that legitimizes their influence on public opinion, promotes judicial accountability, and exerts pressure on public policy. However, the digital arena is not entirely democratic, as the distribution of digital capital and the visibility of information remain shaped by platform algorithms, influencers, political buzzers, and actors possessing greater accumulations of capital. These findings demonstrate that the social practices of netizens emerge from the dynamic interaction between habitus, capital, and the digital field, as conceptualized by Bourdieu, while also highlighting that digital space functions as both a site for the reproduction and contestation of power in contemporary society.